Collaboration Of Pharmacy Personnel With Health Personnel Services Of Rsau Dr. Norman T. Lubis Lanud Sulaiman To Accelerate The Health Recovery Of Tni Soldiers And Their Families - Wigatiningsih, Ratih; Arman , Andi; Bahari, Samsul (Jurnal Syntax Fusion, 2025)
Collaboration between pharmaceutical and medical staff at Norman Lubis Hospital plays a crucial role in supporting quality healthcare services for soldiers and their families. This study aims to identify and analyze the challenges in this collaboration and to formulate strategies for enhancing its effectiveness. The primary focus of the research is to support the safe and effective use of medications, particularly in the care of Indonesian Air Force personnel at Sulaiman Air Base. Findings reveal that the main challenges to collaboration include differences in organizational and professional cultures, limited resources, lack of interprofessional training, rigid hierarchy, and restrictive policies. Miscommunication and a lack of role understanding due to cultural differences often exacerbate the situation. Resource constraints in both personnel and infrastructure increase workloads, while the military hospital's hierarchical structure limits pharmacists' roles in decision-making. To address these obstacles, policy changes, interprofessional training programs, and resource improvements are needed. These steps are expected to strengthen collaboration and enhance the quality of healthcare services in military hospitals, thus accelerating the health recovery of soldiers.